Research progress of main microflora and their roles during strong-flavor Baijiu Daqu fermentation - HE Xiaorong, ZHANG Qing, TANG Jiahuan, LIU Pei (Zhongguo niangzao)
Daqu, as an important saccharification and fermentation starter in Baijiu brewing, is rich in a wide variety of stable microorganisms during the fermentation, which provides complex and diverse enzymes, flavor (precursor) substances and microflora for distiller's grains fermentation. In this paper, the main microbial sources in the fermentation process of strong-flavor (Nongxiangxing) Baijiu Daqu, the changes of microorganisms in different fermentation stages, the role of important functional microorganisms, and the methods of microbial community analysis were reviewed, in order to provide scientific basis for optimization of strong-flavor Daqu production process and improvement of Baijiu quality.